Precipitation changes of Valdivia city (Chile) during the past 150 years - González-Reyes, Álvaro; Muñoz, Ariel A (BOSQUE, 2017)
Extensive records of rainfall are considered fundamental for analysing potential current climate change especially in zones where ecosystems are highly humidity dependent. Valdivia city has the longest instrumental record in the nation, starting in 1853, though including a lapse between 1880 and 1899. The present study had the main objective of evaluating changes in precipitation in annual, seasonal and monthly periods and distribution extreme values from 1901 to 2005; further, the activity of global scale climate forcing, such as ENSO and AAO, over the precipitation. Additionally, we have filled this gap period with other instrumental historical registers and Araucaria araucana Tree Ring chronology by evaluated rainfall shifts since 1853. Annual, seasonal and monthly decreases were registered between 1901 and 2005. Especially significant for 1853 - 2005, 1901 - 2005, autumn and September. Negative extreme values (droughts) were more frequent in the second half-century, compared with positive extreme values obtained prior to 1950. A high concentration of negative values was also registered post-1980, especially in autumn and winter. Significant and negative correlations were registered between the SOI indexes of ENSO, with a strong relationship across the year, except in summer. The AAO has registered negative and significant relationships as well, particularly during autumn, and February and March. These decreases suggest an extension of summer-time conditions in Valdivia for longer intervals, concentrating precipitation in winter.